Electronic and Vibrational Spectral Studies ofPentafluoro-Benzoic Acid and Pentafluoro-Benzonitrile - Gupta, S.P.; Garg, A. (Asian Journal of Chemistry, 2010)
The infrared and Raman spectra of pentafiuorobenzonitrile and pentafluorobenzoic acid and the near ultraviolet spectra of the vapours of pentafluorobenzonitrile corresponding to 1A1g → 1B2u and 1A1g → 1B1u transitions of benzene are reported. Assignments of fundamentals are proposed. Spectra in various polar and non-polar solvents are also reported in the ultraviolet region and the effect of solvents and pH discussed.